Immediate effects of different trunk exercise programs on jump performance - Imai, A.; Kaneoka, K.; Okubo, Y.; Shiraki, H. (International Journal of Sports Medicine, 2016)
The aim of this study was to investigate the immediate effects of trunk stabilization exercise (SE) and conventional trunk exercise (CE) programs on jump performance. 13 adolescent male soccer players performed 2 kinds of jump testing before and immediate after 3 experimental conditions: SE, CE, and non-exercise (NE). The SE program consisted of the elbow-toe, hand-knee, and back bridge, and the CE program consisted of the sit-up, sit-up with trunk rotation and back extension. Testing of a countermovement jump (CMJ) and rebound jump (RJ) were performed to assess jump performance. Jump height of the CMJ and RJ-index, contact time, and jump height of the RJ were analyzed. The RJ index was improved significantly only after SE (p=0.017). However, contact time and jump height did not improve significantly in the SE condition. Moreover, no significant interaction or main effects of time or group were observed in the CMJ. Consequently, this study showed the different immediate effect on the RJ between the SE and CE, and suggested the possibility that the SE used in this study is useful as a warm-up program to improve the explosive movements.